Pengaruh Brand Image Dan Harga Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus Pada Cafe Litchi Di Malang) - Saputri, Vicky Yuli; Arifin, Rois; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of this research is to determine the influence of Brand Image and price on customer loyalty through customer satisfaction as an intervening variable. This type of research is explanatory research using a quantitative approach. Sampling was carried out by distributing questionnaires to Cafe Litchi customers using the Slovin formula so that a sample of 86 respondents was obtained. This research method uses simple regression analysis with the SPSS analysis tool. Partially, this research shows that Brand Image has an effect on Customer Satisfaction, Brand Image has an effect on Customer Loyalty, price has an effect on Customer Satisfaction, price has an effect on Customer Loyalty, Brand Image has an effect on customer loyalty through customer satisfaction, price has no effect on customer loyalty through customer satisfaction, and customer satisfaction influences customer loyalty. Keywords: Brand Image, price, customer loyalty, customer satisfaction, cafe shop